Identification of a Novel Transcription Factor TP05746 Involved in Regulating the Production of Plant-Biomass-Degrading Enzymes in Talaromyces pinophilus - Zhang, Ting; Liao, Lu-Sheng; Li, Cheng-Xi; Liao, Gui-Yan; Lin, Xiong; Luo, Xue-Mei; Zhao, Shuai; Feng, Jia-Xun (Frontiers in Microbiology, 2019)
Limited information on transcription factor (TF)-mediated regulation exists for most filamentous fungi, specifically for regulation of the production of plant-biomass-degrading enzymes (PBDEs). The filamentous fungus, Talaromyces pinophilus, can secrete integrative cellulolytic and amylolytic enzymes, suggesting a promising application in biotechnology. In the present study, the regulatory roles of a Zn2Cys6 protein, TP05746, were investigated in T. pinophilus through the use of biochemical, microbiological and omics techniques. Deletion of the gene TP05746 in T. pinophilus led to a 149.6% increase in soluble-starch-degrading enzyme (SSDE) production at day one of soluble starch induction but an approximately 30% decrease at days 2 to 4 compared with the parental strain ΔTpKu70. In contrast, the T. pinophilus mutant ΔTP05746 exhibited a 136.8–240.0% increase in raw-starch-degrading enzyme (RSDE) production, as well as a 90.3 to 519.1% increase in cellulase and xylanase production following induction by culturing on wheat bran plus Avicel, relative to that exhibited by ΔTpKu70. Additionally, the mutant ΔTP05746 exhibited accelerated mycelial growth at the early stage of cultivation and decreased conidiation. Transcriptomic profiling and real-time quantitative reverse transcription-PCR (RT-qPCR) analyses revealed that TP05746 dynamically regulated the expression of genes encoding major PBDEs and their regulatory genes, as well as fungal development-regulated genes. Furthermore, in vitro binding experiments confirmed that TP05746 bound to the promoter regions of the genes described above. These results will contribute to our understanding of the regulatory mechanism of PBDE genes and provide a promising target for genetic engineering for improved PBDE production in filamentous fungi.